2016
DOI: 10.18632/oncotarget.12470
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 23 dysregulates late sodium current and calcium homeostasis with enhanced arrhythmogenesis in pulmonary vein cardiomyocytes

Abstract: Fibroblast growth factor 23 (FGF23), elevated in chronic renal failure, increases atrial arrhythmogenesis and dysregulates calcium homeostasis. Late sodium currents (INa-Late) critically induces ectopic activity of pulmoanry vein (the most important atrial fibrillation trigger). This study was to investigate whether FGF23 activates the INa-Late leading to calcium dysregulation and increases PV arrhythmogenesis. Patch clamp, western blot, and confocal microscopy were used to evaluate the electrical activities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 43 publications
(49 reference statements)
0
26
0
Order By: Relevance
“…Our study found an increased NCX current with a larger sodium influx through the I Na‐Late in CKD PV cardiomyocytes. The increase of calcium transient by I Na‐Late enhancer ( Anemonia sulcata toxin) in control PV cardiomyocytes and the decrease of calcium transient by ranolazine in CKD PV cardiomyocytes suggests that I Na‐Late can induce calcium overload and contribute to the faster PV spontaneous activity …”
Section: Discussionmentioning
confidence: 99%
“…Our study found an increased NCX current with a larger sodium influx through the I Na‐Late in CKD PV cardiomyocytes. The increase of calcium transient by I Na‐Late enhancer ( Anemonia sulcata toxin) in control PV cardiomyocytes and the decrease of calcium transient by ranolazine in CKD PV cardiomyocytes suggests that I Na‐Late can induce calcium overload and contribute to the faster PV spontaneous activity …”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies demonstrated direct detrimental cardiac effects of FGF23 including LVH [ 65 ], cardiac fibrosis [ 84 ], cardiac mechanical dysfunction [ 90 ] and cardiac arrhythmias [ 91 ]. Of note, these off-target effects of FGF23 are Klotho-independent.…”
Section: Cardiac Effects Of Middle Moleculesmentioning
confidence: 99%
“…A strong independent association between FGF23 levels and atrial fibrillation have been demonstrated in both CKD [ 101 ] and non-CKD [ 100 , 102 ] populations. The mechanism of FGF23-induced atrial fibrillation has been demonstrated in pulmonary vein cardiomyocytes of which the ectopic activity is the most important trigger of atrial fibrillation [ 91 ]. Treatment with FGF23, pulmonary vein cardiomyocytes showed a faster beat rate, larger late sodium currents and calcium transient (together with larger sodium-calcium exchanger and L-type calcium currents) and a greater increase in mitochondrial reactive oxygen species (ROS) expression than non-treated cells; all of these effects are inhibited by an inhibitor of late sodium currents.…”
Section: Cardiac Effects Of Middle Moleculesmentioning
confidence: 99%
See 2 more Smart Citations